Sistem Pendukung Keputusan Rekomendasi Dalam Pemilihan Pemeliharaan Ikan Air Tawar Ekonomis Menerapkan Metode Additive Ratio Assesment (ARAS) - Agus Iskandar (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Developing a business in fresh water is a promising business, because food ingredients such as fresh water fish are always needed by every community. Freshwater fish are fish that live in fresh water, such as living in lakes, rivers and so on. if someone wants to build a freshwater business, then the type of freshwater fish that is suitable and the easiest to maintain must be chosen. The many types of freshwater fish make prospective business owners confused in choosing which type of water fish is suitable for business. In helping the owner solve these problems, a decision support system is needed. A decision support system is a system developed on a computer, where the development uses computer-based steps or methods. SPK requires a method in its application. The method used in this study is the ARAS method. The ARAS method is an acronym for the Additive Ratio Assessment Method (ARAS). The ARAS method is the method used in ranking each alternative by using the reference, namely the criteria as the calculation material. By using the SPK using the ARAS method, the result is that by using the ARAS method, the selection of freshwater fish that is highly recommended to be kept is Alternative A1 with the type of fish, namely catfish as the best alternative.